Answer:
(-1, 0), (-1, -5)
Explanation:
The initial translation transformation was ...
(x, y) ⇒ (x +4, y)
Then the reflection across the line y=x added the transformation ...
(x, y) ⇒ (y, x)
So, the result of the composition of transformations was ...
(x, y) ⇒ (y, x+4)
Then the reverse transformation, the one that gets from the image back to the pre-image, will be ...
(y, x+4) ⇒ (x, y)
(x, y) ⇒ (y-4, x)
The points A", B", C", D" will be transformed back to pre-image points ...
A"(-4, 5) ⇒ A(1, -4)
B"(-1, 5) ⇒ B(1, -1)
C"(0, 3) ⇒ C(-1, 0) . . . . . . matches an answer choice
D"(-5, 3) ⇒ D(-1, -5) . . . . . matches an answer choice